22.3: Multi‐ Fingerprint Capacitive sensor with Transparent, Low‐cost Solution. (26th August 2021) - Wang, Linzhi; Xi, Kerui; Qin, Feng; Lin, Baiquan; Su, Ping; Gong, Shun; Peng, Xuhui
Abstract : A capacitive fingerprint sensor based on panel manufacturing is developed. It enables greater identification at a lower cost. The larger area allows for more feature points to be collected, and Multi‐finger identification can also be realized. Since no optical components are required, the capacitive fingerprint sensor is lighter and thinner than the optical fingerprint sensor. Transparency is also one of its strengths.